Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.2166/wpt.2013.036
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for water reuse in the Kraft pulp and paper industry

Abstract: The reuse of wastewater by the pulp and paper industry reduces environmental impacts by contributing to raw water conservation, thereby making a greater volume of fresh water available for nobler purposes, and reducing wastewater treatment. This study evaluated a proposed system of water reuse at a Kraft pulp and paper plant in Brazil, based on a survey of water quality required by its consumption points, supplied by its water treatment plant. Results after ultrafiltration included: turbidity of 0,3 NTU and pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Primary treatment removes them via sedimentation. Furthermore, recovered fibers can be reused in paper manufacturing (Kossar et al, 2013 ; Tilha et al, 2019 ). Parts of the inorganic dissolved substances are sodium salts and bleaching agents (Mandeep et al, 2019 ), while dissolved organic substances are mostly lignin and hemicellulose fragments, and extractives, many of which are chlorinated due to the bleaching step with chlorine dioxide (Cabrera, 2017 ; Hubbe et al, 2016 ).…”
Section: Characteristics Of Raw Effluentmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary treatment removes them via sedimentation. Furthermore, recovered fibers can be reused in paper manufacturing (Kossar et al, 2013 ; Tilha et al, 2019 ). Parts of the inorganic dissolved substances are sodium salts and bleaching agents (Mandeep et al, 2019 ), while dissolved organic substances are mostly lignin and hemicellulose fragments, and extractives, many of which are chlorinated due to the bleaching step with chlorine dioxide (Cabrera, 2017 ; Hubbe et al, 2016 ).…”
Section: Characteristics Of Raw Effluentmentioning
confidence: 99%
“…Some process steps need freshwater, while others require low-quality water (Li et al, 2016 ). Analyzing an industrial wastewater treatment plant, Kossar et al ( 2013 ) suggested reusing ultrafiltration-polished effluent in kraft paper machine showers and vacuum pumps, because the water does not enter into contact with the produced paper. The authors highlighted that the color of the treated effluent was the limiting factor for its reuse.…”
Section: Reuse Of Treated Effluentsmentioning
confidence: 99%
“…Many authors have studied ultrafiltration as the main treatment to remove the dissolved and colloidal substances (DCS) concentrated during the recycling of white waters not treated by using biological treatment. The results show that in pulp and paper mill effluent (white water), DCS are considered to be the major membrane foulants [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Biological process will modify organic substances presents in white waters and also will produce new organic substances from biological sludge. Hence, a good knowledge of characteristics substances present in these waters is important to help minimize membrane fouling (Kossar et al, 2013), aiming to obtain high quality water from UF filtration that may replace fresh water use in some applications. Furthermore, in the literature investigations about foulants characteristics had received little attention in comparison with studies focused on membrane performance and water quality.…”
Section: Resultsmentioning
confidence: 99%